Displaced epicenters: Notes for listening to Latin American cinemas - Kratje, Julia (Nawi, 2021)
This work investigates theoretical contributions of three Latin American authors –the problem of form according to Nora Catelli, the cultural criticism according to Nelly Richard and figuration according to Ana Amado– that approach comparative studies of Latin American cinemas from feminist perspectives. The article takes into account aesthetic issues, cultural differences and social asymmetries that cross the circulation of research paradigms in the international academic field.